Improved burn wound healing by the antimicrobial peptide LLKKK18 released from conjugates with dextrin embedded in a carbopol gel. (15th October 2015) - Silva, João P.; Dhall, Sandeep; Garcia, Monika; Chan, Alex; Costa, César; Gama, Miguel; Martins-Green, Manuela
Graphical abstract: Abstract: Antimicrobial peptides (AMPs) are good candidates to treat burn wounds, a major cause of morbidity, impaired life quality and resources consumption in developed countries. We took advantage of a commercially available hydrogel, Carbopol®, a vehicle for topical administration that maintains a moist environment within the wound site. We hypothesized that the incorporation of LLKKK18 conjugated to dextrin would improve the healing process in rat burns. Whereas the hydrogel improves healing, LLKKK18 released from the dextrin conjugates further accelerated wound closure, and simultaneously improving the quality of healing. Indeed, the release of LLKKK18 reduced oxidative stress and inflammation (low neutrophil and macrophage infiltration and pro-inflammatory cytokines levels). Importantly, it induced a faster resolution of the inflammatory stage through early M2 macrophage recruitment. In addition, LLKKK18 stimulated angiogenesis (increased VEGF and microvessel development in vivo ). Moreover, collagen staining evaluated by Masson's Trichrome was visually much more intense after treatment with LLKKK18, suggesting higher collagen deposition. Overall, we generated an effective, safe and inexpensive formulation that maintains a moist environment in the wound, easy to apply and remove, and with potential to prevent infection due to the presence of an antimicrobial peptide. These findings propel us to further study this LLKKK18-containing formulation, setting the foundations towards a potential therapeutic approach for burn wound treatment. Statement of Significance: This work presents a newly developed formulation that holds great potential as a therapeutic approach for burn treatment. It is based on the sustained delivery of an antimicrobial peptide – LLKKK18 – from conjugates with dextrin, after degradation of dextrin backbone upon exposure to wound α-amylases. Conjugates were further embedded in Carbopol®, a commercially available hydrogel, suitable for topical administration and that provides a moist environment to the wound. Overall, we obtained an efficient, safe and non-expensive formulation that improves burn wound healing, maintains a moist environment within the wound, is easy to apply-and-remove, and has potential to prevent infection due to the presence of an antimicrobial peptide. Importantly, this is the first time the wound healing ability of LLKKK18 is demonstrated and that its main mechanisms of action are identified.